At the intersection of information literacy and written communication: Student perspectives and practices related to source-based writing - Dahlen, Sarah P.C.; Nordstrom-Sanchez, Kelsey; Graff, Nelson (The Journal of academic librarianship, 2024)
Source-based writing exists at the intersection of information literacy and written communication, where information from sources is incorporated into writing to achieve a communicative purpose. This case study addresses how students in junior-level college writing classes use information from sources in their papers and how they think about these practices. Student papers from multiple disciplines were coded to document source-based writing practices, such as the use of direct quotes, paraphrasing, and summarizing, and the rhetorical purpose the cited information served in the paper. The papers exhibited high use of direct quotes, indirect citations, and information from sources used as background information. Student perspectives on these practices were gathered through focus groups, with prominent themes being a predilection for efficiency, negative associations with source-based writing, and desire for detailed assignment prompts. Implications for teaching are discussed. •Junior-level papers analyzed and focus groups conducted•Papers exhibited high use of direct quotes and indirect citations.•Information from sources most often used as background information•Students prioritize practices perceived to be efficient.•Many students have negative associations with source-based writing.